Intralabyrinthine Schwannomas: Disease Presentation, Tumor Management, and Hearing Rehabilitation - Choudhury, Baishakhi; Carlson, Matthew L.; Jethanamest, Daniel (Journal of Neurological Surgery Part B: Skull Base, 2019)
Intralabyrinthine schwannomas (ILS) are rare tumors that frequently cause sensorineural hearing loss. The development and increased use of magnetic resonance imaging in recent years have facilitated the diagnosis of these tumors that present with otherwise nondiscriminant symptoms such as tinnitus, vertigo, and hearing loss. The following is a review of the presentation, pathophysiology, imaging, and treatment with a focused discussion on auditory rehabilitation options of ILS.
Keywords: intralabyrinthine schwannoma; intracochlear schwannoma; intravestibular schwannoma; primary inner ear schwannoma; dizziness; tinnitus; hearing loss; auditory rehabilitation; inner ear masses